2007
DOI: 10.1007/s11096-007-9097-z
|View full text |Cite
|
Sign up to set email alerts
|

Does hospitalisation affect hypnotic and anxiolytic drug prescribing?

Abstract: Hospital appeared to have a significant impact on delayed HA use in the French general population. Our results should incite hospital prescribers to transversally reconsider the whole sleep disorder treatment strategy in hospital settings, from improving patient's accommodation conditions, to working out a consensus on the justification of prescription of HA and precising the exact place of nursing team in sleep disorders management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…Microscopic studies have shown that specialists, in particular hospitalists, influence the prescribing behaviour of general practitioners (GP), directly by initiating treatments or indirectly by informing GPs about drugs [1][2][3][4][5][6][7][8][9][10][11]. Hospitalization of patients is also the occasion to take stock of their drug regimen and very frequently results in changes in medications [12][13][14][15][16][17][18][19][20][21]. However, some modifications are not clinically motivated and are only made to match the hospital formulary.…”
Section: Introductionmentioning
confidence: 99%
“…Microscopic studies have shown that specialists, in particular hospitalists, influence the prescribing behaviour of general practitioners (GP), directly by initiating treatments or indirectly by informing GPs about drugs [1][2][3][4][5][6][7][8][9][10][11]. Hospitalization of patients is also the occasion to take stock of their drug regimen and very frequently results in changes in medications [12][13][14][15][16][17][18][19][20][21]. However, some modifications are not clinically motivated and are only made to match the hospital formulary.…”
Section: Introductionmentioning
confidence: 99%
“…In our retrospective study on prison patients, we observed a frequency of psychoactive substance use of 21.5% in 2000 that remained stable at 20.6% in 2004 and that was confirmed near 20% in 2008 (Jonker and Cabelguenne, personal communication). These results can be compared to the 25-30% frequency found in the French general population [2]. In France, in 2001, the rate of prisoners affected by mental disorders was estimated as 30% [16].…”
Section: Bdz Use In Psychiatric Practicementioning
confidence: 96%
“…Of these, the anxiolytics were found to be the most frequently used. Among the general French population, 25–30% is classed as occasional or regular users and 5–7% as chronic users of hypnotics or anxiolytics like benzodiazepine (BDZs) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Despite their risks, BZDs are widely prescribed in the general population. In France, 25%‐30% of the population are regular or occasional users and 5‐7% are chronic users . BZD consumption is particularly frequent in prison, where approximately 20% of male prisoners are treated by BZDs .…”
Section: What Is Known and Objectivementioning
confidence: 99%